PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR BAHASA INGGRIS KELAS V SDN 064973 BHAYANGKARA - Wulan Kurnia Denti; Robenhart Tamba (STKIP Subang, 2025)
This study was motivated by the low English learning outcomes of fifth-grade students at SDN 064973 Bhayangkara, caused by monotonous teaching, limited media, and low student engagement. The aim was to determine the effect of the Problem Based Learning (PBL) model assisted by flash card media on students’ English learning outcomes. The research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. A total of 43 students participated, divided into experimental (class VA) and control (class VB) groups. Instruments included multiple-choice tests, observation sheets, interviews, and documentation. Data were analyzed using normality tests, homogeneity tests, and an independent sample t-test. Results showed that the average post-test score of the experimental class was 78.33, higher than the control class at 62.05. A significance value of < 0.001 indicates a significant effect of the PBL model assisted by flash card on students’ learning outcomes. In conclusion, the model is effective in improving elementary students’ English achievement, especially in the topic Parts of Our Body that Work Together.